2022
DOI: 10.1002/slct.202204050
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibitory Activity and Molecular Docking Study of Selected Natural Phenolic Compounds as AR and SDH Inhibitors**

Abstract: Polyol pathway enzymes, aldose reductase (EC 1.1.1.21; AR, ALR2), and sorbitol dehydrogenase (EC 1.1.1.14; SDH, SORD) have been widely investigated as the enzymes crucially involved in the pathogenesis of several chronic complications, including nephropathy, neuropathy, retinopathy, and cataracts associated with diabetes mellitus. Although phenolic compounds have been reported to possess many other biological activities, in continuation of our interest in designing and discovering potent inhibitors of AR and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…[13][14][15] Enzymes are produced by cellular anabolism, the naturally occurring biological process to make more complex molecules from simpler ones. 16,17 Agricultural enzymes can be defined as biocatalysts that accelerate chemical reactions by breaking down the nutrients in the soil to be easily absorbed by plant roots. Therefore, agricultural enzymes are bioactive proteins that help increase crop production, soil fertility, and food preservation.…”
mentioning
confidence: 99%
“…[13][14][15] Enzymes are produced by cellular anabolism, the naturally occurring biological process to make more complex molecules from simpler ones. 16,17 Agricultural enzymes can be defined as biocatalysts that accelerate chemical reactions by breaking down the nutrients in the soil to be easily absorbed by plant roots. Therefore, agricultural enzymes are bioactive proteins that help increase crop production, soil fertility, and food preservation.…”
mentioning
confidence: 99%
“…In the literature, there are reported that some different phenolic compounds showed a significant inhibitory effect on aldose reductase (AR), sorbitol dehydrogenase (SDH) enzymes, 6‐phosphogluconate dehydrogenase (6PGD), glucose‐6‐phosphate dehydrogenase (G6PD), paroxanase‐1, carbonic anhydrase isozymes hCA I, and hCA II enzymes. Exemplarily, in a recent study, the effects of 4‐methylcatechol, danshensu, esculin, morin, naringin, phloridzin, prunetin, schizandrin, vanillic acid on AR and SDH were examined and it has been shown that these phenolic acids had strong inhibitory effects on activity of AR and SDH enzymes [17–18] . The effect of phenolic compounds on glucose‐6‐phosphate dehydrogenase and 6‐phosphogluconate dehydrogenase enzymes was investigated and it was observed that these compounds showed an inhibition effect at the μM level [19] …”
Section: Introductionmentioning
confidence: 99%
“…Exemplarily, in a recent study, the effects of 4-methylcatechol, danshensu, esculin, morin, naringin, phloridzin, prunetin, schizandrin, vanillic acid on AR and SDH were examined and it has been shown that these phenolic acids had strong inhibitory effects on activity of AR and SDH enzymes. [17][18] The effect of phenolic compounds on glucose-6-phosphate dehydrogenase and 6phosphogluconate dehydrogenase enzymes was investigated and it was observed that these compounds showed an inhibition effect at the μM level. [19] While phenolic compounds offer diverse health benefits, excessive intake can disrupt metabolic processes, potentially harming organisms.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 There has been a noticeable rise in interest in plants recently, as well as the potential for employing natural chemicals derived from plants as medicines. 16,17 We are observing a global resurgence in interest in using botanical therapy and plants in healthcare products because of their significant efficacy in many fields of medicine with few high availability, side effects, and relative ease of acquisition. 18,19 Bromelain is a member of a class of proteolytic enzymes employed orally for the systemic treatment of bloodclotting-related illnesses, inflammation, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the core aims of contemporary pharmacology is the quest for novel physiologically active substances that can exert various effects with little toxicity 14,15 . There has been a noticeable rise in interest in plants recently, as well as the potential for employing natural chemicals derived from plants as medicines 16,17 . We are observing a global resurgence in interest in using botanical therapy and plants in healthcare products because of their significant efficacy in many fields of medicine with few high availability, side effects, and relative ease of acquisition 18,19 …”
Section: Introductionmentioning
confidence: 99%